Annual, seasonal and spatial variation of abundance of the shrimp Artemesia longinaris (Decapoda : Penaeoidea) in south-eastern Brazil - Costa, R. C.; Fransozo, A.; Castilho, A. L.; Freire, FAM (Cambridge University Press, 2005)
The influence of several environmental factors oil the abundance and spatial-temporal distribution of the shrimp Artemesia longinaris were investigated from January 1998 to December 1999 in the Ubatuba region of São Paulo State, Brazil. Collections were performed monthly in the bays of Ubatumirim (UBM), Ubatuba (UBA) and Mar Virado (MV). Six sampling transects were estabilshed in each bay, four were parallel to the shore line, and two were next to the rocky shores. A commercial shrimp fishing boat equipped with two 'double-rig' nets was used. A total of 11,503 individuals was collected, including 1633 from UBM, 6344 from UBA and 3526 from MV the majority of the captured specimens came from the deeper areas (15 to 20 m) with high salinity (34 to 36 ppt). The highest abundance of A. longinaris in Ubatuba bay was recorded in areas where fine and very fine sand comprised more than 70% of the sediment. Moreover, the abundance of A. longinaris followed a seasonal trend, being higher during the summer, when intrusions of cold South Atlantic Coastal Waters (SACW) are frequent. Thus, type of sediment, temperature and salinity are determinant factors in the distribution of A. longinaris in the studied region.